41 Correlation and Reproducibility of Invasive and Non-invasive Haemodynamic Parameters for Identifying Optimal AV Delay in Cardiac Resynchronisation Therapy. (31st May 2014) - Finegold, Judith; Bordachar, Pierre; Kyriacou, Andreas; Afzal Sohaib, SM; Kanagaratnam, Prapa; Ploux, Sylvain; Lim, Boon; Peters, Nicholas; Davies, David Wyn; Lefroy, David; Ritter, Philippe; Francis, Darrel; et al.
Abstract : Background: Acute haemodynamic measurements can be used for AV delay (AVD) optimisation of cardiac resynchronisation therapy (CRT). It is uncertain whether non-invasive measurements are as reliable as those measured invasively. Methods: 37 patients with CRT-P or CRT-D device (86% male, mean age 64 years) had AVD optimisation performed using both invasive and non-invasive systolic blood pressure (SBP) and LV dp/dtmax Results: There was good concordance between optima obtained using non-invasive SBP, invasive LV and aortic SBP: SDD between 5.7 and 14.1 ms, R 2 between 0.86 and 0.95 (Table 1 ). In contrast, the optima derived from maximising LV dp/dtmax did not agree as well with the other optima: SDD between 28.1 and 29.8 ms, R 2 between 0.58 and 0.65. Of the comparisons in all 36 patients, those between LV dp/dtmax and non-invasive SBP (r 2 = 0.58) and between LV dp/dtmax and invasive LV SBP (r 2 = 0.62) were worse (p = 0.0067 and 0.013 respectively) than the comparison between non-invasive SBP and invasive LV SBP (r 2 = 0.88). Test re-test reproducibility was better for invasive and non-invasive SBP; invasive LV SBP (SDD 16.8ms, coefficient of variation COV 10.1) non-invasive SBP (SDD 18.3, COV 11.3), compared to invasive LV dp/dtmax (SDD 23.6, COV 14.6). Conclusions: In this study, we demonstrate good agreement between AVD optimisation performed using non-invasive and invasive systolic blood pressure. LV dp/dtmax showed relatively poor correlation with the AVD optima determined using SBP which is most likely due to a larger noise component in LV dp/dtmax measurements.